Gestational Trophoblastic Neoplasia From Genetically Confirmed Hydatidiform Moles: Prospective Observational Cohort Study. Issue 9 (November 2018) - Usui, Hirokazu; Qu, Jia; Sato, Asuka; Pan, Zijun; Mitsuhashi, Akira; Matsui, Hideo; Shozu, Makio
Abstract : Objective: The aim of this study was to evaluate the incidence and risk factors of gestational trophoblastic neoplasia (GTN) from hydatidiform moles (HMs) cytogenetically diagnosed in a prospective cohort setting. Methods: The prospective observational cohort study included cases of cytogenetically defined molar pregnancies, which were diagnosed by a multiplex short tandem repeat polymorphism analysis. Cases were classified as androgenetic complete HMs (CHMs), diandric monogynic triploid partial HMs (PHMs), or biparental abortion. Gestational trophoblastic neoplasia was diagnosed according to the International Federation of Gynecology and Obstetrics 2000 criteria. Incidences for each category, that is, CHM, PHMs, and biparental abortion, were calculated. Clinical variables (age, partner age, gravidity, parity, height, weight, BMI, and gestational age) and laboratory data (serum human chorionic gonadotropin [hCG], white blood cell count, hemoglobin, and platelet count) were compared between spontaneous remission cases and GTN cases in androgenetic CHMs. Results: Among 401 cases, 380 were classified as follows: 232 androgenetic CHMs, 60 diandric monogynic PHMs, and 88 biparental abortions. A total of 35 cases (15.1%) of CHMs, but only 1 case of PHM (1.7%) and no biparental abortions, exhibited progression to GTN. The hCG value before evacuation was significantly higher in GTN cases than in spontaneous remission cases ( P = 0.001, Kruskal-Wallis test). Patient age was also significantly higher in GTN cases than in spontaneous remission cases ( P = 0.002, Student t test). Conclusions: Under the cohort cytogenetic diagnosis setting, the traditional risk factors for GTN after molar pregnancy, hCG value before evacuation and age, were confirmed in androgenetic CHMs. The risk of GTN was lower for PHMs than for CHMs. However, 1 patient with cytogenetic PHMs developed into GTN. Abstract : Supplemental digital content is available in the text.